BILINGUAL AND MONOLINGUAL LEARNERS: A COMPARATIVE STUDY - Umedova Oyxon Sultonovna (International Journal of Literature and Language Studies, 2026)
This study examines the differences between bilingual and monolingual learners in terms of cognitive development, academic performance, language skills, and social competence. Bilingual learners are individuals who use two languages regularly, whereas monolingual learners use only one language. Recent research has shown that bilingualism may provide cognitive advantages such as enhanced problem-solving abilities, greater mental flexibility, and improved attention control. However, bilingual learners may also face challenges related to vocabulary development in each language. This comparative study reviews existing literature and discusses the strengths and limitations of both learner groups. The findings suggest that bilingual learners generally demonstrate stronger executive functioning and intercultural communication skills, while monolingual learners often show greater depth of vocabulary in their single language. The study highlights the importance of educational strategies that support both groups of learners.